Evaluation of filter design and harmonic analysis using PSCAD/EMTDC - Aimi Shakira, Yuseh (2010)
Nowadays, electricity becomes one of the most important necessities to the world. Designing of filter is one of the methods to improve power quality in delivering electrical power to the customer. This project presents the evaluation of filter design and harmonic analysis to the system network. Here, it helps the utility system by increase the capability to power supply with fewer losses. The IEEE test system are used in this project as a base line diagram before any analysis which is load flow analysis, transient stability analysis, harmonics analysis according to active filter that approach to the system. The 4-bus test system and 9-bus test system analyzed by using MATLAB and PSCAD. Generally, power transmission and distribution are design for operation with sinusoidal voltage and current waveform at a constant frequency. However, when nonlinear load such as thyristor drives, converters and arc furnace are connected to the system, excessive harmonic currents are generated and this causes both current and voltage distortion. The active filter concept uses power electronics to produce harmonic components which cancel the harmonic components from the nonlinear loads. Evaluation of harmonics filter is crucial to make sure the filter is in optimum design, not under or over design. The result shows the effectiveness of active filter design modeling by PSCAD software and analysis the harmonic in simulation part. As a conclusion, the active filter that design improved the quality of the power system network in distributed electricity to the customer.